ANALISI BIAYA TRANSPORTASI MINIMUM DI PT SAMUDERA LINE DI SAMARINDA - Lekatompessy, Aris Rainer Devane (EKONOMIA, 2019)
Minimum Transportation Cost Analysis at PT Herlin Samudera Line Samarinda (Empirical Study at PT Herlin Samudera Line Company Period 2017). under guidance of Mrs. Elfreda Apolonia Lau as First guide and Mrs Eka Yudhyani as second guide. This research aims to know and analyze the cost of coal production of PT HERLIN SAMUEDRA LINE transported from the production area, JT Bina Mitra Muara Kembang, kuala tungkal, and redu surabaya to the destination area of Berau, batam, north Jamrud and jasatama gresik the problem in this research is whether the transportation cost incurred by PT Herlin samuedra Line has not done the transportation method. the basic theory used in this research is operational management that focuses on transportation. This research hypothesis is coal transportation cost from production source of JT Binamitra, kuala tungkal and redu surabaya to destination area of batam, berau, north jamrud and Jasatama gresik PT HERLIN SAMUDERA LINE not yet optimal.The analysis tool used in this research is North west corner method and modified Method.The result of the research shows that the transportation cost is based on the calculation of PT SAMUDERA LINE of Rp 94,209,640 while the calculation of transportation cost based on the calculation of modified method amounted to Rp 80,527,326 resulting in a decrease in transportation cost of Rp 13,682,314. The results of this research indicate that the hypothesis of this research states that the cost of transportation of coal has not been optimally accepted or the hypothesis of this research is accepted.